Sustainable Marketing, as a Buyer’s Motivating Factor in the Retail Business: Example of Georgia - Taktakishvili, Tengiz; Sachaleli, Nino (European Scientific Journal, ESJ, 2023)
During the recent years, sustainability has appeared to be the challenge for the business sector and especially in the retails one. The business owners are still doubting about producing sustainable products, as it needs its segment and marketing strategies. The article highlights the importance of sustainable marketing in the retail’s sector and discusses it as a motivating factor, from the customers’ site. The main aim of the article is to study the role of sustainable marketing and create the profile of “sustainable buyers” on example of Georgia. The article according to the quantitative research method studies how sustainable marketing has influence on buyers’ choice and proofs the hypothesis that sustainable marketing is a motivation factor in the retail sector, that has a huge influence on the decision-making process.